Type 2 Diabetes Increases Risk of Unfavorable Survival Outcome for Postoperative Ischemic Stroke in Patients Who Underwent Non-cardiac Surgery: A Retrospective Cohort Study - Zhang, Faqiang; Ma, Yulong; Yu, Yao; Sun, Miao; Li, Hao; Lou, Jingsheng; Cao, Jiangbei; Liu, Yanhong; Niu, Mu; Wang, Long; Mi, Weidong (Frontiers in Aging Neuroscience, 2022)
OBJECTIVE Diabetes mellitus (DM) has been critically associated with unfavorable outcomes in the general population. We aimed to investigate the association between type 2 DM and long-term survival outcomes in the patients with perioperative ischemic stroke. RESEARCH DESIGN AND METHODS This was a retrospective cohort study of patiens who had suffered from perioperative ischemic stroke between January 2008 to August 2019. Diabetic individuals were included in perioperative ischemic stroke patients with DM group. The outcome of interest was long-term overall survival (OS). We conducted propensity score matching (PSM) and inverse probability treatment weighting (IPTW) to adjust for baseline characteristic different between groups. Multivariate Cox regression analysis with step-wise selection to calculate the adjusted hazard ratio (HR) of OS and type 2 DM. RESULTS During a median follow-up of 46.2 months (interquartile range [IQR], 21.1,84.2), 200 of 408 patients (49.0%) died. The overall survival rates at 3 yr ,5 yr and 10 yr were significantly lower for perioperative ischemic stroke patients with DM than those without DM (3 yr OS: 52.2% vs 69.5%, P < 0.001; 5 yr OS: 41.6% vs 62.4%, P < 0.001; 10 yr OS: 31.1% vs 56.6%, P < 0.001). All covariates were between-group banlanced after using PSM or IPTW. The perioperative ischemic stroke patients with type 2 DM had a shortened OS in primary analysis (HR, 1.947; 95% CI, 1.397-2.713; P < 0.001), PSM analysis (HR, 2.190; 95% CI, 1.354-3.540; P = 0.001), and IPTW analysis (HR, 2.551; 95% CI, 1.769-3.679; P < 0.001). CONCLUSIONS Type 2 DM was associated with an unfavorable prognosis for overall survival in the patients with perioperative ischemic stroke. When perioperative ischemic stroke co-occured with Type 2 DM, the potential synergies would have multiplicative mortality risk Further research to assess the adverse effects of type 2 DM on the long-term survival may be warranted.